PENERAPAN LOGOTERAPI DALAM PSIKOEDUKASI KESEHATAN MENTAL BAGI PERSONEL KEPOLISIAN: UPAYA PENCEGAHAN STRES DAN BURNOUT - Adelia Melenia; Anissa Salsabila; Denis Natalia Siburian; Galang Putra Yudha Pradana; Gene Meshani; Oktari Anggi Setya (CV. Adiba Aisha Amira, 2025)
The police profession is known for its high levels of occupational stress and psychological risk. Exposure to traumatic events and institutional pressure makes police personnel vulnerable to stress and burnout. This community service activity aims to enhance the psychological resilience of members of the Metro Bekasi City Police through logotherapy-based psychoeducation. Logotherapy, an existential approach, emphasizes the search for life’s meaning as a source of motivation and mental endurance. The method used was an interactive lecture supported by a psychoeducational module developed from Viktor Frankl’s theory. The materials covered the basic concepts of logotherapy, the principle of meaning in suffering, and practical strategies for maintaining psychological resilience. Evaluation was conducted through pretests and posttests to assess participants’ understanding. The results indicated an increase in participants' awareness of the importance of values and meaning in coping with occupational stress. This psychoeducational intervention not only improved knowledge but also served as a preventive strategy for police mental health development. Logotherapy proves to be a relevant humanistic approach that empowers officers to view their duties as meaningful life missions.